Ensuring 'safe use' of biotechnology: key challenges - Gupta, Aarti (2002)
Governing safe use of biotechnology in agriculture is a controversial new regulatory challenge facing developing countries such as India. This article identifies short-and long-term challenges to biosafety governance in India and emphasises the need for institutional mechanisms to ensure that use of biotechnology can fulfil desired societal goals. Although biosafety regimes are critical, they cannot substitute for broad institutional fora to debate the social implications of the use of biotechnology in agriculture. - Reproduced.
Keywords: Biotechnology; Agricultural biotechnology